(untitled) (Medicine Today, 2017)
This cross sectional study was done in different upazillas of Sylhet district during July 2009 to June 2011 to find out the prevalence & common risk factors of rickets below 15 years in Sylhet district. The children under 15 years of age were selected from villages/slums by multistage random sampling. After recognition of at least one feature of rickets, the cases were sent to SOMCH or Upazilla Health Complex. They were examined by investigator and suspected cases were selected for further investigation. After radiological and biochemical examination the final cases were analyzed. In this study the prevalence of rickets in Sylhet district is 0.097%. Male children were more affected than female. In this study regarding feeding habit rice was the stable food which was eaten more than one time by all the rachitic children. Only twenty five percent of children drank milk once a day. The prevalence of rickets in Sylhet district was 0.097% which was almost similar to other parts of Bangladesh. Common risk factors for developing rickets are low socio-economic condition and carbohydrate rich dietary habit. Medicine Today 2017 Vol.29(2): 13-16